Establishing a Canadian national clinical trials network for kidney disease: proceedings of a planning workshop. Issue 1 (December 2015) - Rigatto, Claudio; Walsh, Michael; Zalunardo, Nadia; Clase, Catherine; Manns, Braden; Madore, François; Samuel, Susan; Morgan, Catherine; Wolfs, Wim; Suri, Rita
Abstract Knowledge generation through randomized controlled trials (RCTs) is critical to advance the medical evidence base, inform decision-making, and improve care and outcomes. Unfortunately, nephrology has typically lagged behind other medical specialties in this regard. The establishment of formal clinical trial networks can facilitate the successful conduct of RCTs and has significantly increased the number of RCTs performed worldwide in other medical specialties. No such formal network of nephrology trialists exists in Canada. On April 24, 2014, the Canadian Kidney Knowledge Translation and Generation Network (CANN-NET) Clinical Trials Committee held a stakeholder engagement meeting to address this gap and improve the nephrology clinical trial landscape in Canada. The meeting was held in Vancouver in association with the 2014 Canadian Society of Nephrology Annual General Meeting and was co-sponsored by the Kidney Foundation of Canada and CANN-NET. Attendees included nephrologists from university- and non-university-affiliated nephrology practices, administrators, and representatives from the Kidney Foundation of Canada. Through structured presentations and facilitated group discussions, the group explored the extent to which nephrology trials are currently happening in Canada, barriers to leading or participating in larger investigator-initiated trials, and strategies to improve clinical trial output in nephrology in Canada. The themes and action items arising from this meeting are discussed. Abrégé La création d'un bagage de connaissances commun par la conduite d'essais cliniques est essentielle pour assurer l'avancement des notions de base en médecine, étayer la prise de décisions, améliorer les soins aux patients et assurer de meilleurs résultats cliniques. L'établissement d'un réseau officiel et reconnu de partage des connaissances issues d'essais cliniques peut en faciliter la conduite et assurer leur bon déroulement. La preuve en est faite par l'augmentation du nombre d'essais cliniques probants ayant été menés à travers le monde, dans d'autres disciplines médicales. Malheureusement, la néphrologie tire de l'arrière à cet égard par rapport aux autres spécialités, un tel réseau de partage n'existe pas dans le domaine au Canada. C'est dans ce contexte que le 24 avril 2014, le comité des essais cliniques de la « Canadian Kidney Knowledge Translation and Generation Network » (CANN-NET) a tenu une assemblée générale afin de mobiliser les parties intéressées. On a voulu leur exposer cette lacune, tenter d'apporter des solutions et ultimement, faire progresser le bilan de la néphrologie en cette matière. La conférence, en collaboration avec l'assemblée générale annuelle de la Société canadienne de néphrologie, s'est tenue à Vancouver et était subventionnée conjointement par la Fondation canadienne du Rein et le CANN-NET. Parmi les participants, on comptait des néphrologues pratiquants associés ou non à un établissement universitaire ainsi que des administrateurs et des représentants de la Fondation canadienne du Rein. À l'aide de présentations structurées et de discussions de groupe, les participants ont pu observer l'état actuel des essais cliniques au pays, identifier les barrières entravant la participation à plus grande échelle à des essais entrepris sous l'initiative d'un chercheur, et discuter de stratégies pour améliorer les résultats d'essais cliniques en néphrologie au Canada. Le présent article fait état des thèmes abordés lors de cette assemblée et des mesures à prendre pour atteindre les objectifs fixés.